The Literatur Review: Hubungan Kadar Hemoglobin terhadap Lama Rawat Inap Pasien Laparotomi: - - Buana, Faris Agung; Darwis, Iswandi; Marcellia, Selvi; Susianti, Susianti (Medula, 2025)
Hemoglobin is an important protein in the blood whose job is to transport oxygen to body tissues. Low hemoglobin levels (anemia) in laparotomy patients can affect postoperative recovery time, including the duration of hospitalization. This study aims to evaluate the relationship between pre-operative hemoglobin levels and length of stay in laparotomy patients. Data were obtained from medical records of patients who underwent laparotomy at the hospital, including hemoglobin levels before surgery, length of stay, and additional variables such as Body Mass Index (BMI) and Surgical Apgar Score (SAS). The analysis showed that patients with low hemoglobin levels had a greater risk of experiencing longer hospital stays. This is due to suboptimal oxygen supply to the tissue, thereby slowing wound healing and increasing the risk of complications, such as infection and organ failure. Treating anemia with blood transfusions or iron supplementation has proven effective in increasing hemoglobin levels and speeding up patient recovery, with the average length of stay reduced to less than four days. Apart from hemoglobin levels, factors such as BMI, SAS, level of complexity of surgery, and the patient's health condition also influence the length of treatment. These findings emphasize the importance of monitoring and correcting hemoglobin levels before surgery as a preventive measure to speed recovery, minimize complications, and reduce hospital operational burden, especially in health facilities with limited resources. Further research is needed to determine the most effective clinical interventions in managing anemia in preoperative patients.